2008
DOI: 10.1107/s1600536808024562
|View full text |Cite
|
Sign up to set email alerts
|

N-(2-Methylphenyl)benzenesulfonamide

Abstract: Key indicators: single-crystal X-ray study; T = 299 K; mean (C-C) = 0.004 Å; R factor = 0.040; wR factor = 0.106; data-to-parameter ratio = 12.8.In the title compound, C 13 H 13 NO 2 S, the conformation of the N-H bond is anti to the ortho-methyl group on the aniline ring, in contrast to the syn conformation observed with respect to the ortho-chloro group in N-(2-chlorophenyl)-benzenesulfonamide. The dihedral angle between the two benzene rings is 61.5 (1) . Molecules are linked into chains running along the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 9 publications
5
16
0
Order By: Relevance
“…The the N-H bond is trans to one of the S-O double bonds ( Fig. 1), similar to what is observed in N-(2-methylphenyl)-benzenesulfonamide (N2MPBSA) (Gowda et al, 2008) and other aryl sulfonamides (Perlovich et al, 2006;Gelbrich et al, 2007;). The two aromatic rings are rotated relative to each other by 44.9 (1)°, compared with the value of 61.5 (1)° in N2MPBSA.…”
Section: S1 Commentsupporting
confidence: 77%
See 2 more Smart Citations
“…The the N-H bond is trans to one of the S-O double bonds ( Fig. 1), similar to what is observed in N-(2-methylphenyl)-benzenesulfonamide (N2MPBSA) (Gowda et al, 2008) and other aryl sulfonamides (Perlovich et al, 2006;Gelbrich et al, 2007;). The two aromatic rings are rotated relative to each other by 44.9 (1)°, compared with the value of 61.5 (1)° in N2MPBSA.…”
Section: S1 Commentsupporting
confidence: 77%
“…The two aromatic rings are rotated relative to each other by 44.9 (1)°, compared with the value of 61.5 (1)° in N2MPBSA. The other bond parameters in N26DMPBSA are similar to those observed in N2MPBSA and other N-(aryl)-sulfonamides (Gowda, Babitha et al, 2007;Gowda, Foro et al 2007;Gowda et al 2008;Perlovich et al, 2006;Gelbrich et al, 2007) (Table 1) is shown in Fig. 2.…”
Section: S1 Commentsupporting
confidence: 75%
See 1 more Smart Citation
“…The amino H atom is trans to one of the O atoms of the SO 2 group (Fig. 1), similar to that observed in N-(2,6-dimethylphenyl)-benzenesulfonamide (Gowda et al, 2008a), N-(2-methylphenyl)-benzenesulfonamide (Gowda et al, 2008b) and other aryl sulfonamides (Perlovich et al, 2006;Gelbrich et al, 2007;Gowda et al, 2008c). The two benzene rings are tilted relative to each other by 64.8 (1)°, compared with the values of 44.9 1…”
Section: Data Collectionsupporting
confidence: 76%
“…BTG thanks the Alexander von Humboldt Foundation, Bonn, Germany, for extensions of his research fellowship. In the present work, as part of a study of the substituent effects on the crystal structures of N-(aryl)-arylsulfonamides (Gowda et al, 2008a(Gowda et al, , 2008b(Gowda et al, , 2008c, the structure of N-(2,3-dimethylphenyl)-benzenesulfonamide has been determined.…”
Section: Data Collectionmentioning
confidence: 99%